PENGARUH CORPORATE GOVERNANCE, RASIO KEUANGAN DAN CASH POSITION TERHADAP KEBIJAKAN DIVIDEN - Wahyudi, Arif (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to analyze the influence of good corporate governance, financial ratio and cash position to the dividend policy. Good corporate governance variables consist of managerial ownership and institutional ownership. Financial ratio variables which are used in this research are profitability (ROA), Liquidity (CR), and Leverage (DER). This research has found some evidences that managerial ownership, institutional ownership, profitability, liquidity, leverage, and cash position simultaneously have significant influence to the dividend policy. The result of research shows that managerial ownership, institutional ownership, profitability variables partially have influence to the dividend policy. While, liquidity, leverages, and cash position variables have no influence to the dividend policy. Keywords: Corporate Governance, Financial Ratio, Cash Position